Constrictive pericarditis 20 years after surgical aortic valve replacement. (8th October 2021) - Nishizawa, Toshinori; Ro, Shosei; Asano, Taku; Tamura, Tomohide
Abstract : Catheterization of the right side of the heart shows an elevated right ventricular pressure, a prominent "y" descent, known as Friedreich's sign, and a dip‐and‐plateau configuration.